A retrospective review with prospective follow up of renal function, blood pressure and proteinuria post living donor nephrectomy at Groote Schuur Hospital, Cape Town South Africa - Murugan, Ashley (Department of Medicine, 2020)
Introduction: Renal transplantation is the treatment of choice for patients with end stage renal disease [ESRD]. An increased risk of ESRD has been demonstrated when comparing donors to age matched healthy non-donors. There are no outcome data in Africa on long term donor renal function or mortality. Therefore, this study aimed to assess long term health complications in the living donor population and evaluate risk factors associated with poor health outcomes of the donors. Methods: This was a retrospective review with prospective follow up of persons undergoing living related donor nephrectomy for renal transplantation, at Groote Schuur Hospital (GSH) from January 2005 to November 2017. We retrospectively analysed baseline demographics, clinical information including blood pressure and renal function (creatinine, eGFR and proteinuria) and compared them with follow up blood pressure and renal function. Results: The majority of the donors were of mixed ancestry 94/154(61%) and 1st degree relatives 111/154 (72%) of which 63/111 (56.8%) donors were siblings. Hypertension developed in 16/31 (51.6%) donors at follow-up. Those developing hypertension had a higher mean baseline blood pressure (systolic blood pressure 139±11.3 mmHg and diastolic blood pressure 85.5±7.3 mmHg). 21/49(42.9%) developed chronic kidney disease [CKD], of which, 16 donors had an eGFR < 60 ml/min/1.73m2 . In those that developed CKD there was a higher percentage of males (p=0.018) and they were older (p=0.048) at baseline. Baseline systolic and diastolic blood pressures was not statistically different in those that developed CKD. 3/31(9.6%) donors developed diabetes. Conclusions: In South Africa, CKD is on the rise and the need for kidney donors for patients with ESRD is therefore also increasing. This study demonstrates that our living donors are at increased risk of CKD and hypertension and therefore need to be followed up more rigorously.